HUBUNGAN USIA SAAT MENOPAUSE, ASUPAN LEMAK JENUH DAN LINGKAR PINGGANG DENGAN TEKANAN DARAH PADA LANSIA WANITA DI POSBINDU FLAMBOYAN II KOTA BEKASI TAHUN 2020 - Nida Amalia (2020)
The elderly population was incresed from time to time and there was shift in disease pattern from infectious desease to degerative desease. One degerative desease often occurred in elderly was incresed blood pressure or hypertension. This study aims to analyzed the relationship of age at menopause, saturated fat intake and waist circumference with blood pressure in elderly women in Posbindu Flamboyan II Bekasi City. This study used a cross sectional approach, taken with a total sampling technique of 40 respondents. Data collection by filled out the questionnaire through interview and measurement directly. Processing data used Pearson correlation test and Spearman Rank test. Based on statistical test result, there was no relations between age at menopause, saturated fat intake with systolic blood pressure (p-value=0,650 and 0,183) and between age at menopause, saturated fat intake with diasolic blood pressure (p-value=0,270 and 0,333). There was relations between waist circumference with systolic and diatolik blood pressure (p-value=0,008 and 0,020). Age at menopause had negative correlation with blood pressure although saturated fat intake and waist circumference had positive correlation. These results were expected to encourage older women to maintain health by adopting healthy lifestyle.